Konstruksi Naratif Gerard Genette dalam Novel Celestial Bodies : Studi Wacana Naratif - Atana Rika; Sutaman; Nur Hasaniyah; Abdus Saat (ELOQUENCE : Journal of Foreign Language, 2025)
Background: This study highlights the significance of narrative structure in revealing cultural identity and ideology, focusing on Celestial Bodies by Jokha Alharthi, a complex novel yet rarely analyzed through Genette’s narratological lens. Purpose: The purpose of this study is to examine the application of Genette’s narrative theory in revealing the structural and ideological dimensions of Celestial Bodies. Method: This research applied a qualitative descriptive method with a narrative discourse analysis approach. The data source was the full text of the novel Celestial Bodies, which consists of 58 chapters named after different characters. The sample was chosen purposively due to its narrative intricacy. Data collection was conducted through intensive close reading, while the analysis employed Genette’s five narrative categories: order, duration, frequency, mood, and voice. The analytical process involved identifying, classifying, and interpreting the narrative techniques and focalization shifts across chapters. Results and Discussion: The results revealed that the novel makes use of narrative fragmentation, including flashbacks (analepsis), flashforwards (prolepsis), internal focalization, and a dual narration style—heterodiegetic and homodiegetic (through Abdullah). These elements are utilized not only to enrich the plot but also to reflect themes of historical memory, gender conflict, and social transition in Oman. This study helps address a lack of structural analysis in Arabic literature and demonstrates the cross-cultural applicability of Genette’s theory. Conclusions and Implications: In summary, the novel shows how narrative techniques can act as vehicles for deeper ideological expression. This research suggests that future studies should continue applying narratological models to diverse literary traditions to uncover global patterns of storytelling and representation.